Development of Scaffolding Based Buzz Group Models to Improve the Study Ability of Students in PGSD Program Study, University of PGRI Yogyakarta - Noormiyanto, Faiz; Setianingsih, Dwi (Journal of ICSAR, 2020)
This research is to develop a scaffolding-based Buzz Group Model, a combination of the Buzz Group Model with sign language and based on the scaffolding principle of Vygotsky. In other words, divide students into small groups, and each group is given one sign language expert. Each group was given the task to solve the problem using sign language. The Buzz Group model is a teaching model by creating small groups of three to six people, and each group is given the assignment to complete an assignment, then ends by delivering the results of the group discussion to other groups. The purpose of this research is to develop a Buzz Group Model that combines the Buzz Group Model with sign language and is based on the principle of scaffolding to facilitate students in mastering sign language to improve the sign language ability of PGSD Yogyakarta PGRI Study Program students. The results of the development of scaffolding-based Buzz Group models referring to Borg and Gall's research and development model after expert validation tested showed that students' sign language skills after using the scaffolding-based Buzz Group model that previously 70% of students had sign-language skills were in a low category, to 5%, 34% of students had sign language skills were categorized as less to 27%, and 16% of students had sign language skills were categorized as being 68%. This value indicates that there is an increase in the ability of students' sign language after the use of the Scaffolding Based Buzz Group Conditional model.